Enhancing Junior High School Students’ Vocabulary Achievement Through Online Dictionary - Priendiansah, Yoga; Tasnim, Zakiyah; Sundari, Siti (EFL Education Journal, 2022)
Vocabulary has a very important role in learning English. Without having good ability in vocabulary, learning English cannot be achieved well. Therefore, students’ vocabulary achievement must be enhanced. One of the ways to enhance the students’ vocabulary achievement is by using online dictionary. This classroom action research with cycle model from Kemmis & Mc Taggart aimed to enhance the eighth grade students’ vocabulary achievement by using online dictionary and to know how it could enhance the students’ participation during the teaching and learning process of vocabulary. The research participants were the VIII J students of MTsN 5 Ngawi, East Java, Indonesia. The data were collected by using a vocabulary test and observation during the teaching and learning process of vocabulary. Quantitative and qualitative descriptive analyses were used to analyze the collected data. The research results showed that there was improvement of the students’ vocabulary achievement and their active participation by using online dictionary. The improvement of the students’ vocabulary achievement was from 67.64% of the students got target score in pre-cycle to 82.35% of the students got the target score in the first cycle. The improvement of the percentage of the students’ participation was 75% in pre-cycle to 83.7% in the first cycle. Hence, it is suggested for English teachers to use online dictionary in the process of teaching and learning vocabulary to improve the students’ active participation and their vocabulary achievement.